Pentingnya Sumber Daya Manusia yang Berkualitas dalam Pandangan Islam - Avrellia Dwi Riantini; Resita Dewi; Rizki Amrillah (Departement of Mathematics Education, 2024)
Our understanding of Islam is an open understanding, which because of its openness is inclusive and capable of being a blessing for the universe. This condition is a victory for Islam which is the happiness of every human being and all of His creatures. By adhering to and making Islamic education a reference in activities, it can be ensured that the quality of human resources as described in the Al-Qur'an and Hadith, is clearly visible if implemented according to His instructions. The problem behind this article is that poverty in this country will not stop, and will it have an impact on human resources. The novelty of this article is that human resources start from development, implementation and maintenance from a hadith perspective. The method in this article is analytical qualitative descriptive. The complexity of educational issues on the one hand and the demand to improve the quality of human resources on the other hand mean that educational issues remain interesting to discuss in the hope that this discussion will be able to generate alternative solutions in developing the quality of human resources through Islamic education.